(untitled) (Experimental biology, 2020)
Abstract The article describes the results of vegetation studies of low mountains and mid mountains of northern range (macro slope) of The Zhetysu Alatau (outside the SNNP «Zhongar Alatau»), which conducted in May 2018. The plant communities of this region belong to the steppe type of vegetation. The steppes on the northern macro slope are distributed in the altitude range from 800 to 1400 m above sea level. Three sub-belts are noted in the steppe zone: desert steppes, true steppes and meadow steppes. Desert steppes are widespread on the ridge low-mountains of the western and central parts of the northern macroslope. The belts of true and meadow steppes are distributed by the intermountain plain, more moisture parts of the southern, sometimes western slopes. Phytocoenotic characteristics of main types of vegetation are done for each altitudinal sub-belt. The steppes are rich in forage plants with the participation of medicinal plants, dominated by steppe grasses and forbs (Festuca valesiaca, Helictotrichon desertorum, Stipa capillata, S. pennata, Koeleria cristata, Phleum phleoides). Shrubs are often found in communities (Spiraea hypericifolia, Cotoneaster melanocarpus, Rosa beggeriana, Artemisia sublessingiana and etc.) In the composition of forbs marked: Salvia dumetorum, Achillea millefolium, Tanacetum vulgare, Galium verum, Thymus marschallianus and etc.). Keywords: Zhetysu Alatau mountain, northern macroslope, steppes, plant communities, phytocoenotic characteristics.